Erwachsenenbildung in internationaler Perspektive Grenzen und Chancen - Grotlüschen, Anke; Käpplinger, Bernd; Molzberger, Gabriele; Schmidt-Lauff, Sabine (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2022)
This volume addresses internationalization and internationality of adult education in two ways. On the one hand, it takes an internal perspective on the research landscape by contextualized specific phenomena of internationalization in adult education and learning. On the other hand, externally induced research questions are addressed from the perspective of their internationality. Both reactive and anticipatory dynamics as well as chances and limitations of internationalization become visible.